Cardiac interventions and cardiac surgery and pregnancy. (1st February 2019) - Cauldwell, Matthew; Johnson, Mark; Jahangiri, Marjan; Roos-Hesselink, Jolien
Abstract: Both cardiac surgery and cardiac interventions are rare in pregnancy but are generally more common in the developing world. Women with known cardiac disease should receive contemporaneous preconception counselling to assess all risks associated with pregnancy including whether surgery or cardiac interventions may need to be considered prior to pregnancy. Some women may need to undergo emergency surgery or procedures during pregnancy and decisions regarding this should be multidisciplinary including cardiologists, cardiac surgeons, anaesthetists, obstetricians and neonatologists. In this review we discuss both conditions where surgery or percutaneous interventions may need to be considered and both the outcomes for the mother and her baby.